Ineffectiveness of pruning to control citrus huanglongbing caused by Candidatus Liberibacter americanus - Lopes, Silvio Aparecido; Frare, Guilherme Fernando; Yamamoto, Pedro Takao; Ayres, Antonio Juliano; Barbosa, Jose Carlos (Springer, 2007)
The huanglongbing (HLB) disease of citrus trees, caused by Candidatus Liberibacter asiaticus and Ca. Liberibacter americanus, was first reported in Brazil in March, 2004. The presence of the disease has caused serious concerns among growers. Pruning experiments were conducted to determine if removal of symptomatic branches or the entire canopy (decapitation) would eliminate infected tissues and save HLB-affected trees. Pruning was done in five blocks on a total of 592 3- to 16 year-old 'Valencia', 'Hamlin' or 'Pera' sweet orange trees showing no symptoms or with two levels of symptom severity. Ten decapitated trees per block were caged and all trees were treated with insecticides to control the psyllid vector, Diaphorina citri. Mottled leaves reappeared on most symptomatic (69.2%) as well on some asymptomatic (7.6%) pruned trees, regardless of age, variety, and pruning procedure. Presence of the pathogen (Ca. Liberibacter americanus) in all symptomatic trees was confirmed by PCR. In general, the greater the symptom severity before pruning the lower the percentage of trees that remained asymptomatic after pruning.
Keywords: greening; inoculum source; Diaphorina citri; disease management